Politik Hukum Pembentukan Peraturan Perundang-Undangan Pasca Perubahan Kedua Undang-Undang Nomor 12 Tahun 2011 - Febriani, Nadia Ayu; Wasti, Ryan Muthiara (Ajudikasi : Jurnal Ilmu Hukum, 2023)
Article 22A of the 1945 Constitution of the Republic of Indonesia mandates the establishment of a rule regarding the law-making process, which serves as a guideline for the law-making process from its inception until the regulation is enacted to the public. However, in its implementation, problems are still related to the law-making process in Indonesia. This normative research uses a statutory and conceptual approach that specifically looks at "over regulated" or "legal obesity” to analyze the legal politics of the formation of laws and regulations after the second amendment of Law Number 12 of 2011 concerning the Establishment of Laws and Regulations. In this context, there is an overlap between one law and another, which creates sectoral egos and results in legal uncertainty in its application. One of the causes of this legal obesity is the lack of regularity in the law-making process. In this case, legislators do not always refer to the guidelines for the law-making process and the principles for forming statutory regulations as stipulated in the law-making process regulation. In addition, the law still needs to be optimal in fulfilling meaningful participation. Therefore, the author will analyze the politics of law of the amendments of law-making process regulation after the Constitutional Court Decision Number 91/PUU-XVIII/2020, which includes accommodating the omnibus method and the concept of meaningful community participation as a solution for overlapping legislation in Indonesia.